Business Groups and Corporate Governance: Review, Synthesis, and Extension. (22nd December 2015) - Colli, Andrea; Colpan, Asli M.
Abstract: Manuscript Type: Review Research Question/Issue: This article addresses the diverse and fragmented literature about the corporate governance of business groups. We collected scholarly work on the subject, proposed a conceptualization of the main research questions they addressed, classified them according to their research themes, and identified future research directions. Research Findings/Insights: Academic research on corporate governance in business groups has been increasing but is still a developing field. Available analyses make use of the main theoretical frameworks in general in corporate governance research. However, there are several areas of analysis that still need stronger conceptualization and empirical work, leaving many opportunities for future studies and a pressing need to substantiate and extend the findings of previous studies. Theoretical/Academic Implications: Our study identifies four avenues for future research on corporate governance in business groups. This includes the examination of the complex relationships and co‐evolutionary processes among corporate governance attributes and organizational and performance outcomes of business groups; the effects of ownership goals on groups' performance outcomes; the role and the actual functioning of boards inside business groups; and the analyses of cross‐national comparison and long‐term development of the governance of business groups. Practitioner/Policy Implications: This research allows practitioners and policymakers to get a better understanding of the crucial areas regarding business groups and their governance, and offers pathways to examine inside the "black‐box" of business groups.